PERBANDINGAN METODE TSUKAMOTO, METODE MAMDANI DAN METODE SUGENO UNTUK MENENTUKAN PRODUKSI DUPA (Studi Kasus : CV. Dewi Bulan) - SUARDIKA, KOMANG WAHYUDI; GANDHIADI, G.K.; HARINI, LUH PUTU IDA (E-Jurnal Matematika, 2018)
This research aims at knowing the comparison among Tsukamoto method, Mamdani method, and Sugeno method in deciding the production of incense at CV. Dewi Bulan. The research discussed about Tsukamoto method, Mamdani method and Sugeno method which consisted of four step, they are: fuzzyfication, forming a fuzzy rules, fuzzy logic analysis, and defuzzyfication. In conclusion, Sugeno method was found to be the best to be used in deciding the number of incense sticks production, comparing with the others. Sugeno method has probability of error value about 1,314%.